Disease simulation interface v.1.0: Operations manual - Callejo, Abel Melquiades; Carvajal, Raphael; Ortega, Kendrix; Pangga, Ireneo; Castilla, Nancy (International Rice Research Institute, 2023)
Disease Simulation Interface (DSI) ver. 1.0 is a software developed by plant pathologists of the Sustainable Impact Platform of the International Rice Research Institute to provide users with an interface to change the inputs, run the simulation, and view the outputs without the need to view or change the source code of the program. It was developed using Electron, a free and open-source software framework for creating desktop applications. It consists of five modules whose links can be accessed through a dashboard. The first module allows the user to customize the settings for accessing the weather database stored in PostgreSQL, an open-source database server. The second allows the selection of locations for which weather data are fetched or retrieved. The third module lets the user download weather data from NASA POWER (https://power.larc.nasa.gov/), an open source website that provides weather data from NASA, and store these in PostgreSQL. The fourth shows a graph of the simulated disease progress during a cropping season in a georeferenced location based on selected weather data. The fifth module allows mapping of the simulated disease epidemics over the area and cropping semester specified by the user. Disease epidemics are computed as area under leaf blast severity or neck blast incidence progress curves which summarizes or integrates the leaf blast severity or neck blast incidence, respectively, during a cropping season. The epidemics are computed for every 20-m x 20-m cell (20-m resolution) in the map based on the daily weather data during the season. The duration of the cropping season starts from the specified date of crop establishment until harvest of the test variety used in the developing the models.